Short-term effects of SARS-CoV-2 infection and return to sport on neuromuscular performance, body composition, and mental health — A case series of well-trained young kayakers - Deng, S.; Deng, J.; Yin, M.; Li, Y.; Chen, Z.; Nassis, G. P.; Zhu, S.; Hu, S.; Zhang, B.; Li, Y. (Journal of Exercise Science & Fitness, 2023)
Purpose This study aimed to examine the short-term effects of SARS-CoV-2 infection and return to sport (RTS) on neuromuscular performance, body composition, and mental health in well-trained young kayakers.